(x+2)(x)(3)=0

Simple and best practice solution for (x+2)(x)(3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+2)(x)(3)=0 equation:


Simplifying
(x + 2)(x)(3) = 0

Reorder the terms:
(2 + x)(x)(3) = 0

Reorder the terms for easier multiplication:
3x(2 + x) = 0
(2 * 3x + x * 3x) = 0
(6x + 3x2) = 0

Solving
6x + 3x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '3x'.
3x(2 + x) = 0

Ignore the factor 3.

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2

Solution

x = {0, -2}

See similar equations:

| 4(x+21)=-3(x-21) | | 49x^2+49x+10=0 | | 128s^2+320s+200= | | 96r^2+336r+294= | | 3(6)-5y=15 | | 8(8x-3)=32x | | -7x-14=5x | | 2d^2+20d+50= | | 3s^2-8s=0 | | 4(x+1)+60=-4x | | 6+5y=9 | | w^2+14w+49= | | 3x-2=-13 | | 4r^2+23r+15= | | 21b^2-57b-18= | | 9b^2-15b-6= | | -4x^2-30x-14= | | 8(3x-4)=2(12x+3) | | 6a^2+79a+50= | | -26w=-7 | | 36v^2+84vt+49t^2=0 | | 6-19a+10a^2= | | 2(7+5x)=9x-4 | | 6+17n-1=9n+33-6n | | 0=-3x^2+8x-2 | | 0=-x^2-5x-2 | | 4w^3+9w^2+5w= | | x+3x=10-2 | | 6x^2+19x+10= | | 81s^2-100=0 | | 0=-x^2-3x+3 | | 8x^3y^3-1= |

Equations solver categories